The polynomial expression in two variables
f ( x , y ) = x 5 + 3 y 2 − 3 x 2 + y 5
can be factorized into the product of two non-constant polynomials with integer coefficients, namely
f ( x , y ) = g ( x , y ) × h ( x , y ) .
Evaluate ∣ g ( 2 , 2 ) ∣ + ∣ h ( 2 , 2 ) ∣ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice! Sweet and simple.
Simple but awesome !!!!
Can someone explain this step by step? I'm having a lot of problems understanding this. Thanks!
Log in to reply
I made some typos: in particular, the third line should read h ( x , y ) = g ( x , y ) f ( x , y ) . You can substitute in the expressions for f and g and find the exact polynomial h , but I omitted that step because it's not necessary to evaluate h at a single point.
Once you find g and h , the two factors of f , finding the final answer is only a matter of plugging in ( 2 , 2 ) and evaluating the desired expression.
Brilliant
WOW
How did you know that g(x,y) = (x+y)?
Log in to reply
Because x + y ∣ x 5 + y 5 and x + y ∣ x 2 − y 2
or you can just 'guess' in this special case because of the symmetry, that f(x,y)=0 when x=1 and y=-1. From the remainder/factor theorem, this means that x-1+y-(-1) must be a factor i.e. x+y is a factor. Not so elegant but still a method of getting there.
Because the polynomial is 0 when x = -y
it's very confusing!right?
y=3x+2 change it to standard form
Consider f ( x ) = x 5 + 3 y 2 − 3 x 2 + y 5 ∴ f ( − y ) = 0
By the factor theorem, we know that ( x + y ) is a factor of f ( x ) ...
Further factorizing f ( x ) , we get... f ( x , y ) = ( x + y ) ( x 4 − x 3 y + x 2 y 2 − x y 3 + y 4 − 3 x + 3 y )
Since, this factorization is irreducible, hence, g ( x , y ) and h ( x , y ) must be ( x + y ) and ( x 4 − x 3 y + x 2 y 2 − x y 3 + y 4 − 3 x + 3 y ) in some order. The order doesn't matter since the problem requires the answer for same values of x and y . Simply plugging in x = 2 and y = 2 in both equation, we get...
∣ g ( 2 , 2 ) ∣ = ∣ 4 ∣ = 4 and ∣ h ( 2 , 2 ) ∣ = ∣ 1 6 ∣ = 1 6
Therefore, ∣ g ( 2 , 2 ) ∣ + ∣ h ( 2 , 2 ) ∣ = 4 + 1 6 = 2 0
this is also my solution.
Good use of the technique Remainder-Factor Theorem , applied to 2 variables.
De x n + y n = ( x + y ) ( x n − 1 ⋅ y 0 − x n − 2 ⋅ y 1 + x n − 3 ⋅ y 3 − . . . − x 1 ⋅ y n − 2 + x 0 ⋅ y n − 1 ) ,
Temos que x 5 + y 5 = ( x + y ) ( x 4 − x 3 y + x 2 y 2 − x y 3 + y 4 )
Segue que,
f ( x , y ) = y 5 + x 5 + 3 y 2 − 3 x 2 f ( x , y ) = ( y 5 + x 5 ) + 3 ( y 2 − x 2 ) f ( x , y ) = ( y + x ) ( y 4 − y 3 x + y 2 x 2 − y x 3 + x 4 ) + 3 ( y + x ) ( y − x ) f ( x , y ) = ( y + x ) ( y 4 − y 3 x + y 2 x 2 − y x 3 + x 4 + 3 y − 3 x ) { g ( x , y ) = x + y h ( x , y ) = y 4 − y 3 x + y 2 x 2 − y x 3 + x 4 + 3 y − 3 x
Por conseguinte,
g ( x , y ) = x + y g ( 2 , 2 ) = 2 + 2 g ( 2 , 2 ) = 4 ∣ g ( 2 , 2 ) ∣ = 4
E,
h ( x , y ) = y 4 − y 3 x + y 2 x 2 − y x 3 + x 4 + 3 y − 3 x h ( 2 , 2 ) = 1 6 − 1 6 + 1 6 − 1 6 + 1 6 + 6 − 6 h ( 2 , 2 ) = 1 6 ∣ h ( 2 , 2 ) ∣ = 1 6
Por fim, ∣ g ( 2 , 2 ) ∣ + ∣ h ( 2 , 2 ) ∣ = 2 0
Factoring out x 5 + y 5 we have:
x 5 + y 5 = ( x + y ) ( x 4 − x 3 y + x 2 y 2 − x y 3 + y 4 )
x 5 + y 5 + 3 y 2 − 3 x 2 = ( x + y ) ( x 4 − x 3 y + x 2 y 2 − x y 3 + y 4 ) + 3 ( y − x ) ( x + y )
Factoring for ( y + x )
x 5 + y 5 + 3 y 2 − 3 x 2 = ( x + y ) ( x 4 − x 3 y + x 2 y 2 − x y 3 + y 4 + 3 ( y − x )
Thus we have
f ( x , y ) = x + y and g ( x , y ) = x 4 − x 3 y + x 2 y 2 − x y 3 + y 4 + 3 ( y − x )
f ( 2 , 2 ) + g ( 2 , 2 ) = 4 + 1 6 = 2 0
Notice that we can write
f ( x , y ) = x 5 + 3 y 2 − 3 x 2 + y 5 = ( x 5 + y 5 ) − ( 3 x 2 − 3 y 2 ) = ( x + y ) ( x 4 − x 3 y + x 2 y 2 − x y 3 + y 4 ) − ( x + y ) ( 3 x − 3 y ) = ( x + y ) ( x 4 − x 3 y + x 2 y 2 − x y 3 + y 4 + 3 x − 3 y )
[It remains to prove that the second factor cannot be factorized further.]
Therefore, g ( x , y ) = x + y and h ( x , y ) = x 4 − x 3 y + x 2 y 2 − x y 3 + y 4 + 3 x − 3 y , so we have ∣ g ( 2 , 2 ) ∣ + ∣ h ( 2 , 2 ) ∣ = 4 + 1 6 = 2 0 .
hint : root of f(x,y) is 0,0 then, f(x,y) is divisible by xy. g(x,y) = xy h(x,y) = f(x,y)/g(x,y)
evaluate the question at point (2,2)
That only implies that (0,0) is the root of one of its factors. Take, for example, f ( x , y ) = x − y . (0,0) is a root of f, but xy is not a factor of f.
Rewrite f ( x , y ) as
( x 5 + y 5 ) + ( 3 y 2 − 3 x 2 )
( x + y ) ( x 4 − x 3 y + x 2 y 2 − x y 3 + y 4 ) + 3 ( y − x ) ( y + x )
( x + y ) ( x 4 − x 3 y + x 2 y 2 − x y 3 + y 4 + 3 y − 3 x ) )
Therefore g ( x , y ) = ( x + y ) and h ( x , y ) = ( x 4 − x 3 y + x 2 y 2 − x y 3 + y 4 + 3 y − 3 x )
And ∣ g ( 2 , 2 ) ∣ + ∣ h ( 2 , 2 ) ∣ = ∣ ( 2 + 2 ) ∣ + ∣ ( 2 4 − 2 3 ∗ 2 + 2 2 ∗ 2 2 − 2 ∗ 2 3 + 2 4 + 3 ∗ 2 − 3 ∗ 2 ) ∣
= ∣ 4 ∣ + ∣ 1 6 ∣ = 4 + 1 6 = 2 0
Input this into Wolfram Alpha:
*
x
5
−
3
x
2
+
3
y
2
+
y
5
*
In alternative forms, you should see this:
( x + y ) ( x 4 − x 3 y + x 2 y 2 − x y 3 − 3 x + y 4 + 3 y )
Replace x and y with 2, as shown below,
( 2 + 2 ) ( 2 4 − 2 3 2 + 2 2 2 2 − 2 × 2 3 − 3 × 2 + 2 4 + 3 × 2 )
then solve ∣ 4 ∣ + ∣ 1 6 − 1 6 + 1 6 − 1 6 − 6 + 1 6 + 6 ∣
Notice the 6's cancel out, as do all but one 16
Now add the remaining numbers ∣ 4 ∣ + ∣ 1 6 ∣
The answer is 20
x^5+y^5=(x+y)(x^4-x^3y+x^2y^2-xy^3+y^4) 3(y^2-x^2)=3(y-x)(y+x)
on observing the eq., it is clear that x=-y is one sol. hence a factor: g(x,y)=(x+y). now, g(2,2)=4 therefore, h(2,2)=f(2,2)/g(2,2)=16 so that h(2,2)+g(2,2)=20
f
(
x
,
y
)
=
x
5
+
y
5
−
3
(
x
2
−
y
2
)
f
(
x
,
y
)
=
(
x
+
y
)
(
x
4
−
x
3
y
+
x
2
y
2
−
x
y
3
+
y
4
)
−
3
(
x
+
y
)
(
x
−
y
)
f
(
x
,
y
)
=
(
x
+
y
)
(
x
4
−
x
3
y
+
x
2
y
2
−
x
y
3
+
y
4
−
3
x
+
3
y
)
Set
g
(
x
,
y
)
=
x
+
y
and
h
(
x
,
y
)
=
x
4
−
x
3
y
+
x
2
y
2
−
x
y
3
+
y
4
−
3
x
+
3
y
g
(
2
,
2
)
=
2
+
2
=
4
h
(
2
,
2
)
=
2
4
−
2
3
×
2
+
2
2
×
2
2
−
2
×
2
3
+
2
4
−
3
(
2
)
+
3
(
2
)
h
(
2
,
2
)
=
1
6
∣
g
(
2
,
2
)
∣
+
∣
h
(
2
,
2
)
∣
=
4
+
1
6
=
2
0
Note that f ( k , − k ) = 0 , hence x + y is a factor by the factor theorem. By the polynomial division we get x + y x 5 + 3 y 2 − 3 x 2 + y 5 = x 4 − x 3 y + x 2 y 2 − x y 3 − 3 x + y 4 + 3 y Hence f ( x , y ) = ( x + y ) ( x 4 − x 3 y + x 2 y 2 − x y 3 − 3 x + y 4 + 3 y ) So ∣ g ( 2 , 2 ) ∣ + ∣ h ( 2 , 2 ) ∣ = 2 0
Problem Loading...
Note Loading...
Set Loading...
x + y ∣ f ( x , y ) ⟹ g ( x , y ) = ( x + y ) ⟹ h ( x , y ) = g ( x + y ) f ( x + y ) g ( 2 , 2 ) = 4 , f ( 2 , 2 ) = 6 4 ⟹ h ( 2 , 2 ) = 1 6 ⟹ ∣ g ( 2 , 2 ) ∣ + ∣ h ( 2 , 2 ) ∣ = 2 0